Pemanfaatan Lahan Sempit Dengan Hidroponik Dutch Bucket System Untuk Mewujudkan Ecogreen-Pesantren Melalui Program Santripreneur Di Pondok Pesantren K.H.A. Wahid Hasyim Bangil Pasuruan - Yuni Lestari; Ari Khusumadewi; Amang Fathurrohman; Hijrin Fitroni; Ubaidillah (LPPM Universitas Yudharta Pasuruan, 2019)
The Islamic Boarding School KHA Wahid Hasyim Bangil, who continues to grow in the field of productive land that turned function into a non-productive land in the form of building construction to fulfill infrastructure facilities in the Islamic Boarding School. In addition, many areas of Islamic Boarding School that have been in paving, so that green land is getting narrower. Through community mentoring with community development approaches, the results of the mentoring process is able to maximize narrow and non productive land into productive land through Dutch Bucket System hydroponics in Islamic Boarding School KHA Wahid Hasyim. This mentoring is also beneficial for the Community assistance by in helping the students in the Islamic Boarding School has fights skills as part of the practice of economic independence, especially in the field of hydroponics with an approach Santripreneur training and counseling guidance.